1995
DOI: 10.2176/nmc.35.438
|View full text |Cite
|
Sign up to set email alerts
|

<I>Correlation Between Magnetic Resonance Images and Histology in Meningiomas: T<SUB>2</SUB>-weighted Images Indicate Collagen Contents in Tissues</I>

Abstract: The magnetic resonance imaging appearance of 40 surgically confirmed intracranial meningiomas was reviewed to correlate signal intensity on T2-weighted images with histological subtypes of meningioma.A moderate variation of signal intensity was found within a given histological subtype. The mean signal intensity scores on T2-weighted images of the fibrous type of meningioma were significantly lower than those of the other types, and were correlated with the collagen content. The signal intensity of meningiomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The majority of authors endorsed the predictive ability of T2WI, noting that tumors hyperintense on T2WI relative to cerebral cortex tended to be softer. [1, 45, 8, 13, 14, 1619, 24, 26, 28, 29]. Yamaguchi et al in their review of 50 patients additionally stated that the probability of a soft tumor is up to 100% higher if hyperintensity on T2WI is associated with hypointensity on T1WI [4].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of authors endorsed the predictive ability of T2WI, noting that tumors hyperintense on T2WI relative to cerebral cortex tended to be softer. [1, 45, 8, 13, 14, 1619, 24, 26, 28, 29]. Yamaguchi et al in their review of 50 patients additionally stated that the probability of a soft tumor is up to 100% higher if hyperintensity on T2WI is associated with hypointensity on T1WI [4].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning tendons, however, training-induced changes in echointensity would imply changes in the amount of collagen fibers, not fat or fluid. Similarly, the signal intensity of magnetic resonance imaging (MRI) has previously indicated the condition of the extracellular matrix, tissue hydration, collagen fiber structure, and proteoglycan content (Erickson et al 1993;Shalabi et al 2002;Soyama et al 1995;Yoon and Halper 2005). Furthermore, T 2 relaxation time of MRI (equivalent to MRI signal intensity) has been shown to correspond to collagen orientation (Du et al 2009;Erickson et al 1993;Nieminen et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[6] Soyama et al . [10] reported on 40 surgically treated intracranial meningiomas, regarding T2 intensity and correlation with histological subtypes. They assigned signal intensity scores on T2 and found that while there was a moderate variation of signal intensity within a given histological subtype, the mean signal intensity scores on T2 of the fibrous type of meningioma were significantly lower than those of the other subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The score correlated with the collagen content and they concluded that meningiomas significantly hypointense to cortex on T2 are composed primarily of fibrous elements. [10] Yrjänä et al . [11] reported on 21 surgically treated meningiomas that had been imaged using a low-field MRI and found that tissue hardness correlated best with relative intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%